Visualization of Intuitionistic Fuzzy B-Spline Space Curve and Its Properties - Abdul Fatah Wahab (Tanjong Malim, 2019)
Visualization of Intuitionistic Fuzzy B-Spline Space Curve and Its Properties by Abdul Fatah Wahab